2006
DOI: 10.2140/jomms.2006.1.881
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic fields at frictionless and frictional cohesive crack tips in quasibrittle materials

Abstract: The lack of any work on the asymptotic fields at the tips of cohesive cracks belies the widespread use of cohesive crack models. This study is concerned with the solution of asymptotic fields at cohesive crack tips in quasibrittle materials. Only normal cohesive separation is considered, but the effect of Coulomb friction on the cohesive crack faces is studied. The special case of a pure mode I cohesive crack is fully investigated. The solution is valid for any separation law that can be expressed in a special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 39 publications
(41 reference statements)
1
37
0
Order By: Relevance
“…It is considered as an additional degree of freedom at relevant enrichment nodes in XFEM. We mention in passing that in [23] complete asymptotic expansions for frictionless and frictional cohesive cracks have been obtained which are analogous to the Williams expansions in brittle solids. These expansions are valid for many commonly used separation laws, e.g.…”
Section: Incremental-secant Modulus Iteration Scheme For Cohesive Cramentioning
confidence: 84%
See 3 more Smart Citations
“…It is considered as an additional degree of freedom at relevant enrichment nodes in XFEM. We mention in passing that in [23] complete asymptotic expansions for frictionless and frictional cohesive cracks have been obtained which are analogous to the Williams expansions in brittle solids. These expansions are valid for many commonly used separation laws, e.g.…”
Section: Incremental-secant Modulus Iteration Scheme For Cohesive Cramentioning
confidence: 84%
“…Although only mode I problems are studied, extension of the scheme to mixed mode problems with or without friction is straightforward. The corresponding enrichment functions (counterparts of (7) and (8) for mode I) can be found in [23].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is remarked, that this type of closure has also been observed in the experiments by Elssner et al (1994) and in the results of an analysis through discrete dislocations around a crack tip by Cleveringa et al (2000). Also, more recently, Xiao and Karihaloo (2006) using the Knein-Williams asymptotic technique, have shown that the crack faces of a pure mode I (frictionless) cohesive crack close in a cusp-like manner.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 53%